Pengembangan Modul Berbentuk Scrapbook pada Materi Sistem Saraf untuk Meningkatkan Hasil Belajar Siswa SMA Kelas XI - Agustina Kiden Lewar*; Suhartini Suhartini (Jurnal Pendidikan Sains Indonesia, 2023)
Nervous system material has a broad scope and is abstract, causing students to have difficulty understanding. One effort that can be made to improve student learning outcomes is to develop learning modules. This research is development research according to Borg and Gall to create a scrapbook module on the nervous system material. The products developed are focused on improving student learning outcomes with data collection procedures including appropriateness tests by material experts and media experts, practicality tests by teachers, and readability tests by students using assessment questionnaires. Items tested include the presentation of the material, conformity with student character, instructions for use, module quality, concept correctness, and student responses. The product validation data obtained is converted to obtain the eligibility category according to Widiyoko. The results of the due diligence by material experts obtained X = 3.8 in the good category, and the due diligence by media experts obtained X = 4.2 in the very good category. While the results of the practicality assessment by the biology teacher obtained X = 4.4 with a very good category and the assessment by students obtained X = 4.3 with a very good category. Based on the results of the feasibility and practicality assessments that were analyzed the scrapbook module was feasible and ready to be used in learning biology specifically on the nervous system material because it met the development requirements